PERANCANGAN SISTEM INSTALASI PEMIPAAN AIR BERSIH PADA GEDUNG PERKANTORAN X 37 LANTAI - Meilyna Andhika Maranatha, (2021)
Plumbing is one of the building utilities that must be considered in the construction of a building because the plumbing system can distribute clean water needed by residents in the building. The design of clean water instaIasi should pay attention to the amount of clean water needs, the volume of the reservoir water tank, pump capacity, pump head, pump power and net positive suction head (NPSH). To be able to meet the needs of clean water in the design of gedun g 37 floors with a total population of 6,975 people, clean water needs of 358 m3/ day. The capacity of the water reservoir tank provided for the lower water tank (Ground Water Tank)is 120 m3 and the upper water tank (Roof Tank)is 30 m3. As a result of the design of the clean water installation, the pipe used has an inner diameter of 138 mm and an outer diameter of 200 mm, the transfer pump capacity is 1.35 m3/ minute with a pump powerof 54 kW.